Is severe early childhood caries predictive of caries and fluorosis in permanent teeth? Ten-year follow-up - Danila Lorena NUNES-; Lúcia de Fátima ALMEIDA DE DEUS MOURA; Marina de DEUS MOURA LIMA; Teresinha SOARES PEREIRA LOPES; Marcoeli SILVA DE MOURA (Universidade Estadual Paulista, 2017)
Abstract Introduction Severe early childhood caries is defined as the presence of any sign of decay in children younger than three years. Objective This retrospective longitudinal observational study investigated caries and fluorosis in children with S-ECC from a city with fluoridated water. Material and method We included children under the age of three years who followed a maternal and child dental care program between the years of 1997 and 2003. The children were divided into 2 groups: group 1 (S-ECC) and group 2 (no caries). Guardians were contacted by telephone or mail. Caregivers completed questionnaire on socio-demographic and behavioral variables. The clinical dental examinations were performed in a dental clinic to assess caries experience and dental fluorosis. Multiple linear regression was used to determine factors associated with DMFT, and multivariate analysis by multiple logistic regression was used to determine the possible independent factors associated with the occurrence of fluorosis. Result The sample consisted of 126 patients aged 8-12 years, of whom 52.4% were male. The presence of S-ECC increased the DMFT by an average of 0.84 (p = 0.02). Both the frequency of tooth brushing and the use of standard toothpaste were protective factors from the development of caries in the permanent dentition (p <0.05). Parents who reported that their children refused to brush their teeth had 70% less chance of developing fluorosis (p = 0.02). Conclusion The presence of S-ECC was a risk factor for the development of caries in the permanent dentition, but not for the development of fluorosis.